Misconceived expectations: Patient reflections on the total knee replacement journey - Bunzli, Samantha; O'Brien, P; Klem, Nardia-Rose; Incoll, I; Singh, J; Davaris, M; Choong, P; Dowsey, M (Wiley-Blackwell, 2020)
Introduction: Fifty per cent of patients consent for total knee replacement (TKR) with unrealistic expectations about what it involves and can achieve. A framework is needed to help surgeons identify key knowledge gaps and misconceptions that can be targeted during the informed consent process. In this qualitative study, we explored knowledge gaps and misconceptions by asking patients to reflect on their expectations along the TKR journey.